RETRACTED: Ammonia Scavenger Restores Liver and Muscle Injury in a Mouse Model of Non-alcoholic Steatohepatitis With Sarcopenic Obesity - Wang, Zi-Xuan; Wang, Meng-Yu; Yang, Rui-Xu; Zhao, Ze-Hua; Xin, Feng-Zhi; Li, Yu; Ren, Tian-Yi; Fan, Jian-Gao (Frontiers in Nutrition, 2022)
Recent studies have revealed that sarcopenia is closely associated with obesity and nonalcoholic steatohepatitis (NASH). However, few attempted to explore the role of sarcopenic obesity in NASH. In this study, we investigated muscular alterations in a rodent NASH model to elucidate their intrinsic relations and explore the potential therapeutic target. Forty-six 8-week-old and sixteen 42-week-old male C57B/L6 mice (defined as young and middle-aged mice, respectively) were fed with a high-fat diet (HFD) for 12 or 20 weeks. A subset of young mice was subjected to ammonia lowering treatment by L-ornithine L-aspartate (LOLA). We examined body composition and muscle strength by nuclear magnetic resonance and grip strength meter, respectively. At the end of the 12th week, all HFD-fed mice developed typical steatohepatitis. Meanwhile, sarcopenia occurred in HFD-fed middle-aged mice, whereas young mice only demonstrated decreased grip strength. Until the end of week 20, young mice in the HFD group exhibited significant sarcopenia and obesity phenotypes, including decreased lean body mass and grip strength, and increased body fat mass and percentage body fat. Additionally, Plasma ammonia level was markedly increased in HFD-fed mice of both ages at week 20. Plasma ammonia level was negatively associated with muscle strength and myofiber diameter in young mice. LOLA can significantly reduce plasma levels of ammonia, alanine aminotransaminase, aspartate aminotransaminase, and cholesterol in mice fed an HFD. Hepatic infiltration of inflammatory cells and collagen deposition area were significantly decreased in HFD group by LOLA treatment. Meanwhile, LOLA significantly increased lean body mass, grip strength, and average muscle fiber diameter of HFD-fed mice. These findings suggest that the occurrence of NASH precedes sarcopenia in HFD mice, and the steatohepatitis-related hyperammonemia might contribute to the pathogenesis of sarcopenia. LOLA might be an effective drug for both steatohepatitis and sarcopenic obesity.